Pengaruh Kinerja Keuangan dan Pertumbuhan Ekonomi terhadap Kinerja Indeks Pembangunan Manusia - Filasti Rahma; Yunarsi; Wilda; Dewi Yulianti (Jurnal Ekonomi & Bisnis, 2022)
Human development is a process of human development that aims to be able to have more choices, particularly in income, health and education dimanasalah of the criterion can be seen through the Human Development Index. The aim of research was to analyze and obtain empirical evidence on the influence of financial performance (fiscal independency, effectiveness of Regional Original Revenue, and expenditure harmony) and economic growth on human development index in Bombana Regency and to find out the most dominant variable influencing human development index. The research was descriptive qualitative study to give a systematic, factual and accurate description on the facts and real condition of financial performance, economic growth, and human development index in Bombana Regency. The data in the research were time series secondary data obtained from library study. They were analyzed using multiple linear regression analysis. The result of the research indicate that fiscal independency, the effectiveness of Regional Original Revenue, expenditure harmony, and economic growth have influence on human development index. Economic growth has the most dominant influence on human development index.